Forkhead box C1 boosts triple‐negative breast cancer metastasis through activating the transcription of chemokine receptor‐4. Issue 12 (18th November 2018) - Pan, Hongchao; Peng, Zhilan; Lin, Jiediao; Ren, Xiaosha; Zhang, Guojun; Cui, Yukun
Abstract : The transcription factor forkhead box C1 (FOXC1) has recently been proposed as a crucial regulator of triple‐negative breast cancer (TNBC) and associated with TNBC metastasis. However, the mechanism of FOXC1 in TNBC development and metastasis is elusive. In this study, overexpression of FOXC1 in MDA‐MB‐231 cells significantly enhanced, whereas knockdown of FOXC1 in BT549 cells significantly reduced, the capabilities of TNBC cell invasion and motility in vitro and metastasis to the lung in vivo, when compared to their respective control cells. Mechanistic studies revealed that FOXC1 increased the expression of CXC chemokine receptor‐4 (CXCR4), probably through transcriptional activation. AMD3100, an inhibitor of CXCR4, could block cell migration. In a zebrafish tumor model, AMD3100 could suppress cell invasion and metastasis. In addition, overexpressing CXCR4 in FOXC1‐knockdown BT549 cells increased the capabilities of TNBC cell invasion and motility. In contrast, inhibition of CXCR4 with either AMD3100 or siRNA in MDA‐MB‐231 cells overexpressing FOXC1 reduced the capabilities of invasion and motility. Taken together, our results reveal a potential mechanism for FOXC1‐induced TNBC metastasis. Abstract : Forkhead box C1 (FOXC1) shows tumor‐promoting activity that increases the growth, invasion, and metastasis of basal‐like breast cancer (BLBC) cells in vitro. Downregulation of CXC chemokine receptor‐4 expression inhibits FOXC1‐induced migration and invasion. FOXC1 could be of value as a potential therapeutic target for BLBC.